Responses of broilers under cold conditioning (15°c) to dietary triiodothyronine and iodine combined to antioxidants, (selenium and vitamin c) - Seven, Ismail; Tatli Seven, Pinar; Yilmaz, Seval (KAFKAS UNIVERSITY, 2009)
This experiment was conducted to determine the influence of dietary antioxidants (selenium (Se) and vitamin C), and triiodothyronine (T3) to iodine on biochemical parameters, malondialdehyde (MDA), catalase (CAT) in broilers exposed cold. In the study, 150, one-day-old, broiler chicks (Ross 308) were used. Chicks were randomized into 1 control and 4 treated groups each containing 30 birds and each experimental group comprised 3 replicates of 10 birds. The experimental groups were as follow: control was fed with basal diet; group I was fed with basal diet supplemented with 1 mg/kg selenium as sodium selenite plus 2 mg/kg iodine as calcium iodate; group II was fed with basal diet supplemented 1 mg/kg selenium plus 1 mg/kg T3; group III was fed with basal diet supplemented with 250 mg/kg vitamin C as ascorbic acid plus 1 mg/kg iodine; group IV was fed with basal diet supplemented with 250 mg/kg vitamin C plus 1 mg/kg T3. Plasma T3, triglyceride and SGPT were significantly different among the groups. MDA level in heart tissue of control group was found significantly higher than those of other groups (P<0.01). MDA levels in liver (P<0.01) and abdominal fat (P<0.001) tissues of control and group I were determined significantly higher than those of other groups, whereas MDA level in lung tissue was similar found in all groups. The CAT activity of liver of control and group I was found significantly the highest (P<0.001). Results showed that cold exposure in broilers induced oxidative damage in tissues, but this damage decreased partly in supplement groups, except group I.
So?uk Koşullar Altındaki (15°C) Broylerlerin Diyetsel Antioksidanlarla (Selenyum ve Vitamin C) Kombine Edilen Triiodotiroidinin ve İyodine Tepkileri
Keywords: Antioxidant enzymes; Ascorbic acid; Broiler; Cold conditioning; Iodine; Selenium; Triiodothyronine